A New Generation of Anime (2000-2020): Evolution, expansion and technical progress in current Japanese animation - Horno López, Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Through the analysis of audiovisual language and the understanding of the creation process of some of the most outstanding anime series of the last decade, this article aims to establish the most representative current aesthetic and technical qualities of this animation model. A set of highlights that could lead to a new stage in the history of Japanese animation, since not only the production techniques have continued to evolve but also its narrative and aesthetics have crossed the border of the established, developing a creation process so efficient that it has become a benchmark for Western productions.